Pengaruh Praktik Kerja Industri dan Motivasi Kerja terhadap Kesiapan Kerja Siswa Keahlian Kelistrikan - Taali Taali; Dian Paramita (Jurnal Pendidikan Teknik Elektro, 2023)
This research was conducted with the aim of knowing how much influence Industrial Work Practices and Work Motivation have on the Work Readiness of Class XI Electrical Engineering Students at SMK Adi Karya Ranah Pesisir. This type of research is descriptive quantitative research with correlation analysis methods. The subjects of this study were class XI Electrical Expertise SMK Adi Karya Ranah Pesisir who had carried out industrial work practices. Data collection uses a questionnaire and documentation, for the instrument scoring system uses a Linkert scale. Before being distributed to the main respondents of the study, the questionnaire was validated by a validator expert lecturer from the Department of Electrical Engineering and also carried out the instrument trial stage to determine the validity and reliability of the instrument through Class XII students of Electrical Skills at SMK Adi Karya Ranah Pesisir. The data analysis technique used multiple linear regression analysis techniques and hypothesis testing using the t-test was carried out to test the effect of each independent variable on the dependent variable, and the f-test was carried out to test the independent variables together on the dependent variable and also carried out a test the coefficient of determination to find out how much the percentage of independent variables influences the dependent variable. The results show that (1) there is a significant and positive effect of industrial work practices on work readiness (2) there is a significant and positive effect on work motivation on work readiness (3) there is a significant and positive effect on industrial work practices and work motivation jointly on work readiness in class XI Electrical Engineering students at SMK Adi Karya Ranah Pesisir.